EVALUATION OF PAPAYA GENOTYPES USING AGRONOMIC DESCRIPTORS AND ESTIMATION OF GENETIC PARAMETERS - Silva, Marcelo de Souza [UNESP]; Leonel, Sarita [UNESP]; Azevedo Souza, Jackson Mirellys [UNESP]; Modesto, Joyce Helena [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Batista Bolfarini, Ana Carolina [UNESP] (Univ Federal Uberlandia, 2018)
In Brazil, the improvement of papaya agribusiness is correlated to the estimation of genetic parameters and evaluation of agronomic descriptors; thus enabling less favourable areas for the development and implementation of papaya crops. Therefore, the current study aimed to evaluate quantitative descriptors and to estimate genetic parameters in genotypes of papaya grown under subtropical climate in the state of Sao Paulo. The experimental design was randomized in block. The experimental units were grouped into seven blocks of five plants each and three treatments, which consisted of three different varieties: Sunrise Solo, Tainung no1 and local. The psychochemical properties were analysed for plant height; intersection height of first fruits; stem diameter; male, female and hermaphroditic flower percentage; fruit number per plant; production; yield; normal fruits percentage, carpeloid and pentandric fruits; pulp matter; pulp length; pulp diameter; pulp shape; pulp cavity; pulp thickness; peel performance; pulp performance; seeds performance; seeds number; soluble solids; pH; titratable acidity; ratio; technological index; ascorbic acid and reducing sugars. Furthermore, most agronomic descriptors showed high heritability; besides that, the varieties Sunrise Solo and Tainung no1 performed the best results in Botucatu.
Keywords: Carica papaya L.; Genetic improvement; Variety's performance; Genetic diversity